Online Sufism and Reestablishing Religious Authority - Hidayati, Dahlia (Universitas Islam Negeri Mataram, 2022)
Recent burgeoning assumptions claim that long-established traditional authorities are professed to diminish due to the rapid advancement of information media technologies. New and more flexible and democratic authorities have dismantled the abovementioned old power. However, contemporary social media transmission does not eradicate these religious authorities, particularly in the realm of Sufism. Sufi figures generally use cyberspace technologies to disseminate and reinforce their doctrines. Based on Weber's theory of charismatic authority, this study examined the authority features manifested by the Sufism figure Habib Luthfi bin Yahya from Pekalongan Indonesia on social media networks. It is encapsulated that the Islamic mystical school of thought is no longer maintained through direct or offline practices, but it has increasingly evolved into an online community. This study focuses on web-based content or online analysis, which means the focus of data collection is based on online sources. Through an analysis of particular usage of the internet and the media exposure about Habib Lutfi, the author explore the use of social media as an important vehicle for Habib Lutfi to strengthen the traditional religious authority.